Pengaruh Sudut Kemiringan Ruang Masak dan Penggunaan Lensa Fresnel terhadap Performa Kompor Surya Tipe Kotak - Risse Entikaria Rachmanita (Jurnal Teknologi Terpadu, 2020)
Performance test on box solar cooker with variations in the inclination angle of the cook room and variations of the cook room cover have been carried out. The variations angle of the cook room are 10°, 20° and 30° while the cook room cover uses 2 variations namely glass and a combination of fresnel glass. The size of the solar cooker is 60 x 60 x 40 cm with a thickness of 0.9 cm. The test was conducted in the car park behind the Engineering Building Politeknik Negeri Jember at 10:00 to 14:00 with recording every 10 minutes. The highest average solar cooker efficiency was found in solar cooker 4 with a cooking room tilt angle of 30° and using a fresnel glass combination cook room cover, the efficiency is 6.7% on the first day of testing. The highest average cooking power was also found in solar cooker 4 of 24.7 W on the second day of testing. The highest water suhue was found in solar cooker 4 at 90°C on the third day of testing.